Io's volcanism controls Jupiter's radio emissions. Issue 4 (11th February 2013) - Yoneda, M.; Tsuchiya, F.; Misawa, H.; Bonfond, B.; Tao, C.; Kagitani, M.; Okano, S.
Abstract: [1] Jupiter's sodium nebula showed an enhancement in late May through the beginning of June 2007. This means Io's volcanic activity and the magnetosphere's plasma content increased during this period. On the other hand, Jupiter's radio emission called HOM became quiet after the sodium nebula enhancement. The HOM emission is considered to be related to the activity of aurorae on Jupiter. These observation results therefore suggest that the increase in plasma supply from Io into Jupiter's magnetosphere weakens its field‐aligned current, which generates the radio emissions and aurorae on Jupiter. By comparing our observation results to recent model and observation results, we add supporting evidence to the possibility that Io's volcanism controls Jupiter's magnetospheric activity. Key points: Brightness of Jupiter's sodium nebula showed an enhancement. HOM activity from Jupiter was weekend after the sodium nebula enhancement. This means abundant plasma from Io weakens Jupiter's magnetospheric activity.